Anti-agalactosyl IgG antibodies in Thai patients with rheumatoid arthritis, systemic lupus erythematosus, and systemic sclerosis - Louthrenoo W. (2014)
This study was performed to determine the prevalence of anti-agalactosyl IgG antibodies in Thai patients with RA, systemic lupus erythematosus (SLE) and systemic sclerosis (SSc), and determine the sensitivity and specificity of anti-agalactosyl IgG antibodies in the diagnosis of RA in comparison with IgM-rheumatoid factor (IgM-RF) and anti-cyclic citrullinated peptide (anti-CCP) antibodies. Serum samples were obtained from 100 patients with RA, 50 cases of SLE, 50 cases of SSc, and 100 healthy controls and analyzed for the presence of anti-agalactosyl IgG antibodies, IgM-RF and anti-CCP antibodies. A serum value greater than mean+2 standard deviation of normal value of anti-agalactosyl IgG antibodies and anti-CCP antibodies was considered positive. The prevalence of anti-agalactosyl IgG antibodies in RA, SLE, and SSc patients was 88.0%, 14.0%, and 12.0%, respectively. The serum level of anti-agalactosyl IgG antibodies in patients with RA (227.10±353.64 AU/mL) was significantly higher than those in SLE (11.84±52.04 AU/mL), SSc (18.85±99.60 AU/mL), and healthy controls (2.14±1.97 AU/mL), (p<0.001). There was a good correlation between the log serum level of anti-agalactosyl IgG antibodies and IgM-RF (r=0.92, p<0.001), anti-CCP antibodies and IgM-RF (r=0.49, p<0.001), and anti-agalactosyl IgG antibodies and anti-CCP antibodies (r=0.55, p<0.001). The sensitivity and specificity in the diagnosis of RA was 88.00% and 96.00% for anti-agalactosyl IgG antibodies, 90.00% and 99.00% for anti-CCP antibodies, and 91.00% and 95.00% for IgM-RF, respectively. The serum level of anti-agalactosyl IgG antibodies was significantly higher in RA than in SLE, SSc, and healthy controls. There was a good correlation between serum levels of anti-agalactosyl IgG antibodies, anti-CCP antibodies, and IgM-RF. These three tests had comparable sensitivity and specificity. © 2009 Clinical Rheumatology.